Woof! : the truth about dogs - Whipple, Annette (Whipple, Annette. Truth about --, 2021)
"How do dogs communicate? Why do dogs sniff butts? Are dogs just tame wolves? These and other questions are answered by the author, along with some extra information provided by the dogs themselves."--